Cooccurrence of Two Different Genetic Diseases: A Case of Valproic Acid Hepatotoxicity in Nicolaides–Baraitser Syndrome (SMARCA2 Mutation)—Due to a POLG1-Related Effect? - Hofmeister, Benedikt; von Stülpnagel, Celina; Berweck, Steffen; Abicht, Angela; Kluger, Gerhard; Weber, Peter (Neuropediatrics, 2020)
Nicolaides–Baraitser syndrome (NCBRS) is a rare disease caused by a mutation in the SMARCA2 gene. Clinical features include craniofacial dysmorphia and abnormalities of the limbs, as well as intellectual disorder and often epilepsy. Hepatotoxicity is a rare complication of the therapy with valproic acid (VPA) and a mutation of the polymerase γ (POLG) might lead to a higher sensitivity for liver hepatotoxicity. We present a patient with the coincidence of two rare diseases, the NCBRS and additionally a POLG1 mutation in combination with a liver hepatotoxicity. The co-occurrence in children for two different genetic diseases is discussed with the help of literature review.
Keywords: Nicolaides–Baraitser syndrome; SMARCA2 mutation; cooccurrence of two genetic diseases; POLG1-related effect; valproic acid hepatotoxicity